Pengaruh Citra Merek dan Kualitas Produk terhadap Keputusan Pembelian Sepeda Motor TVS - Veta Lidya Pasaribu (Business Management Journal, 2022)
This study aims to determine the effect of brand image and product quality individually and jointly on TVS motorcycle purchase decisions for Pamulang University students. The research method uses quantitative methods and uses primary and secondary data types. The population of this research is all Pamulang University students in 2019 by using purposive sumpling technique using the ancient rao formula in determining the number of samples as many as 100 respondents. The data analysis method used validity test, reliability test, classical assumption test (normality test, multicollinearity test, heteroscedasticity test and autocorrelation test), multiple linear regression analysis, correlation coefficient analysis, coefficient of determination (KD) analysis, t test and F test. The results of data analysis show that partially there is a positive and significant influence on brand image on purchasing decisions, with tcount (5.778) > ttable (1.985) and sig ( 0.000)< 0.05, by demi more Ho is rejected and Ha is accepted. Partially there is a positive and significant effect of product quality on purchasing decisions, with a value of tcount (9.247) > t table (1.985) and sig (0.000) < 0.05, thus Ho is rejected and Ha is accepted. Simultaneously there is an effect of Brand Image and product quality together on purchasing decisions, has a very strong relationship with the regression equation Y= 8.618+0.478x1+0.644x2, constant 8.618, coefficient x1 0.478 and coefficient x2 0.644, while the correlation value or r is 0.954 and the coefficient of determination is 0.908 or 90.8% while the remaining 9.2% is influenced by other factors, with Fcount (490.216) > Ftable (3.09) and sig (0.000) < 0.05, thus Ho is rejected and Ha is accepted, meaning that there is a positive and significant influence between Brand Image and product quality on student purchasing decisions on TVS motorcycles.